1996
DOI: 10.1002/(sici)1096-9861(19960115)364:3<473::aid-cne7>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Hybridization histochemical and immunohistochemical localization of inhibin/activin subunits and messenger ribonucleic acids in the rat brain

Abstract: Inhibin and activin are best known as gonadal glycoprotein hormones but have a broad anatomical distribution. We previously described the central distribution ofinhibin/activin beta A- and beta B-subunit proteins in some neuronal cell bodies, fibers, and nuclei of the rat brain and reported a possible role for central activin in suckling-induced oxytocin secretion and corticotropin releasing factor release. In the present report, we mapped the detailed immunohistochemical localization of inhibin/activin alpha-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…Follistatin (FS) is a high affinity binding protein of activin and antagonizes its actions [6][7][8]. Proteins and mRNA of activin and FS show a wide tissue distribution [9][10][11][12][13][14] and both are detected in the central nervous system (CNS, [15][16][17]). …”
Section: Introductionmentioning
confidence: 75%
“…Follistatin (FS) is a high affinity binding protein of activin and antagonizes its actions [6][7][8]. Proteins and mRNA of activin and FS show a wide tissue distribution [9][10][11][12][13][14] and both are detected in the central nervous system (CNS, [15][16][17]). …”
Section: Introductionmentioning
confidence: 75%
“…Embryonic neurons are dependent on the continual presence of growth factors for their survival while adult neurons may require trophic support only in times of injury (Benn and Woolf, 2004). Activin mRNA and protein are present at basal levels throughout the adult brain including cortical regions (Roberts et al, 1996) with significant upregulation of activin mRNA, its protein and activin signals in adult neurons can be detected within hours after injury (our data; Tretter et al, 1996;Dow et al, 2005;Bottner et al, 2006). Because activin administration protects adult hippocampal neurons from excitotoxic kainic acid and quinolic acid addition in vivo Tretter et al, 2000), it seems likely that increased amounts will improve neuronal survival after ischemic injury.…”
Section: Discussionmentioning
confidence: 99%
“…Two type II receptors, ActR-II and ActR-IIB, have been identified (Mathews and Vale, 1993). Expression of mRNA and protein for activin subunits (Roberts et al, 1996) and activin receptor types (Bengtsson et al, 1995;Cameron et al, 1994;Funaba et al, 1997;Morita et al, 1996;Soderstrom et al, 1996) has been demonstrated and partially mapped in the CNS. Both activin subunit mRNAs, ␤A and ␤B, are constitutively expressed in the CNS (Andreasson and Worley, 1995).…”
mentioning
confidence: 95%